Tujuan Utama Pejuang Asing dalam Melawan ISIS di Suriah - Falhan Hakiki; Arfin Sudirman; Dina Yulianti (Andalas Journal of International Studies (AJIS), 2021)
ISIS (Islamic State of Iraq and Syria) is a transnational terrorist organization that has carried out attacks in various countries so that it becomes a threat to the state and society. Initially, ISIS was based in Syria and Iraq and carried out a lot of violence there. ISIS recruits foreign fighters from various countries and is termed “jihadists”. On the other hand, the fight against ISIS is carried out by the state, militia, and foreign fighters. These foreign fighters came to Syria from various countries individually to fight ISIS. This research aims to answer research questions regarding the goals of foreign fighters in fighting ISIS. The research was conducted qualitatively by conducting interviews with a number of informants and then analyzed by coding techniques using Atlas.ti software. The findings of this study are that foreign fighters have individual, ethnic, religious, ideological goals, to stop the occupation, and to overthrow the government.